2006
DOI: 10.1038/sj.jp.7211498
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous administration of darbepoetin to NICU patients

Abstract: Objective: Darbepoetin can be administered either intravenously (i.v.) or subcutaneously (s.c.). However, no information is available regarding pharmacokinetics and pharmacodynamics following its i.v. administration to neonates. Study design:We administered a single i.v. dose (4 mg/kg) of darbepoetin to 10 neonates who had a hemoglobin p10.5 g/dl. Blood was obtained for immature reticulocyte fraction (IRF) and absolute reticulocyte count (ARC), before and 48 h following the dose. Blood was also drawn for pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Evaluation of single-dose pharmacokinetics in preterm infants revealed a similar prolonged half-life. 3,4 Recent studies in animals and humans evaluating the non-hematopoietic effects of ESAs suggest a strong potential for neuroprotection via a variety of mechanisms, including oligodendrogenesis, decreased inflammation, decreased oxidative injury,anddecreasedapoptosis. [5][6][7][8][9] Our group previously reported an increased mental developmental index in former extremely low birth weight (ELBW) infants who had serum Epo concentrations .500 mU/mL, 10 and Neubauer et al reported improved developmental outcomes at 8 to 12 years in former Epotreated preterm infants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of single-dose pharmacokinetics in preterm infants revealed a similar prolonged half-life. 3,4 Recent studies in animals and humans evaluating the non-hematopoietic effects of ESAs suggest a strong potential for neuroprotection via a variety of mechanisms, including oligodendrogenesis, decreased inflammation, decreased oxidative injury,anddecreasedapoptosis. [5][6][7][8][9] Our group previously reported an increased mental developmental index in former extremely low birth weight (ELBW) infants who had serum Epo concentrations .500 mU/mL, 10 and Neubauer et al reported improved developmental outcomes at 8 to 12 years in former Epotreated preterm infants.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, Darbe provided this effect with weekly dosing. Given its significantly longer half-life, 3,4 Darbe may be the more attractive and practical choice of ESA for preterm infants. There were no differences in hearing or visual impairment, but significant differences in the incidence of CP were noted, in that only infants in the placebo group had CP identified by examiners masked to the treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…We used a darbepoetin dose of 4 mg/kg on the basis of our previous pharmacokinetic studies. 3,4 This dose is a much higher unit dose than that given by Buhrer and Obladen. If the conversion factor of 1 mg darbepoetin ¼ 400 U rEpo is used, 4,5 our dose was 6.4 times higher than the Buhrer and Obladen dose.…”
Section: Discussionmentioning
confidence: 85%
“…or subcutaneous (s.c.) route of administration. 3,4 Our recent studies, and unpublished data cited by the manufacturer, 5 suggest that s.c. dosing may be more effective in stimulating erythropoiesis than i.v. dosing, but this has not been tested directly.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 On the basis of our pharmacokinetic studies of darbepoetin administration to VLBW neonates, [15][16][17] we hypothesized that when a neonate qualifies for a late RBC transfusion, a single dose of darbepoetin would counteract the transfusion's erythrosuppressive effect. The single-dose concept was derived from our studies, [15][16][17] and that of Freise et al, 18 who calculated that among VLBW neonates, only a modest increase in plasma erythropoietin is needed to effectuate a several-fold increase in erythropoiesis. With this information, we reasoned that the strategy of single-dose darbepoetin administration accompanying a late transfusion might be worth testing as a means of preventing further NICU transfusions.…”
Section: Introductionmentioning
confidence: 99%